Association of early immune-related adverse events with treatment efficacy of neoadjuvant Toripalimab in resectable advanced non-small cell lung cancer - Tao, Ye; Li, Xiang; Liu, Bing; Wang, Jia; Lv, Chao; Li, Shaolei; Wang, Yuzhao; Chen, Jinfeng; Yan, Shi; Wu, Nan (Frontiers in Oncology, 2023)
Background Neoadjuvant immunotherapy with anti-PD-1 were proved promising in resectable non-small cell lung cancer (NSCLC). Immune-related adverse events (irAEs) have been preliminarily implicated its association with treatment efficacy. Here we elucidated early onset of irAEs associated with better clinical outcome in a prospective study (Renaissance study). Methods We conducted the prospective study of NSCLC patients treated by neoadjuvant Toripalimab (240mg, every 3 weeks) plus platinum-based chemotherapy from December 2020 to March 2022 at Peking University Cancer Hospital. Patients were enrolled if they have resectable IIB-IIIB NSCLC without EGFR/ALK mutation. Data were analyzed to explore the relationship between clinical outcome and irAEs after neoadjuvant treatment. The Renaissance study was approved by Peking University Ethic board (2020YJZ58) and registered at https://clinicaltrials.gov/ as NCT04606303. Results Fifty-five consecutive patients were enrolled with a male to female ratio of 10:1, the median age was 62 years old (IQR: 45-76), of which 44 patients (80%) were diagnosed as squamous cell carcinoma. Forty-eight of 55 patients finally received thoracic surgery with a median preoperative waiting time of 67 days (IQR 39-113 days). Pathological results demonstrated that 31 (64.6%) patients achieved major pathological response (MPR) and 24 (50.0%) achieved complete pathological response (pCR). Among 48 patients who received en bloc resection, immunotherapy-related thyroid dysfunction, rash/pruritus and enteritis occurred in 11 patients (22.9%), 7 patients (14.6%) and 1 patient (2.1%), respectively. Six patients (54.5%) with thyroid dysfunction achieved MPR with 5 (45.5%) achieved pCR, and the median time to onset was 45 days (IQR 21-91days). Six patients (85.7%) with rash or pruritus achieved MPR and 5 patients (71.4%) achieved pCR, with median time to onset was 8 days (IQR 6-29 days). Furthermore, irAEs had no significant influence on operation time (170.6 min vs 165.7 min, P=0.775), intraoperative blood loss (67.4 mL vs 64.3 mL, P=0.831) and preoperative waiting time (93 days vs 97 days, P=0.630) when comparing with patients without irAEs (Figure 3）. Conclusions The immunotherapy-related rash is potentially associated with pathological outcomes in NSCLC patients after neoadjuvant chemo-immunotherapy，suggesting easy-to-find irAEs, such as rash, can be used as indicators to predict response to neoadjuvant chemo-immunotherapy.